Distribution of a rare discomycete Miladina lecithina (Pezizales, Pyronemataceae) in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The paper reports data on the finding of rare operculate discomycete Miladina lecithina (Cooke) Svrček (Pyronemataceae, Pezizales), representative of monotypic genus Miladina Svrček, which was collected during the mycological researches in the National Nature Park «Kremenetsky Gory» (Ternopil Oblast, Ukraine) in 2013–2016. This species was found on water-soaked wood in the stream. Earlier, the species was recorded in Transcarpathian and Kharkiv regions. M. lecithina belongs to the psilopezioid fungi, a group of operculate discomycetes (Pezizales) that inhabit on wet or water-soaked wood in running water. This species is found in different regions of Europe, Asia, South and North America, as well as Puerto Rico, everywhere it is considered rare. This species inherent feature is ability to form the anamorphic stage, known as Actinospora megalospora, which belongs to the group of aquatic hyphomycetes. Such phenomenon is rather unusual for operculate discomycetes, among which pleomorphic representatives are very rare. Detailed morphological characters, locality, ecological peculiarities, collection dates, data on general distribution and original illustrations of M. lecithina are provided. As a result of investigation of specimens deposited in mycologycal herbarium of the M.G. Kholodny Institute of Botany NAS of Ukraine (KW-M) found that M. lecithina was sometimes erroneously cited under the names Humaria aquatica and H. sydowii. It is proposed to exclude H. sydowii from the list of species of the Pyronemataceae family known for Ukraine. As a result of the generalization of the obtained data the information of six currently known localities of the species in Ukraine and a distribution map of M. lecithina are given.
Keywords: Ternopil Oblast, National Nature Park «Kremenetsky Hory», Ascomycota, distribution map, psilopezioid discomycetes.